The poverty of contractarian moral education. Issue 4 (2nd October 2019) - Clayton, Matthew; Stevens, David
ABSTRACT: In A Theory of Moral Education, Michael Hand claims that a directive moral education that seeks to persuade children that a particular conception of contractarian morality is justified can be undertaken without falling foul of the requirement not to indoctrinate. In this article, we set out a series of challenges to Hand's argument. First, we argue that Hand's focus on 'reasonable disagreement' regarding the status of a moral conception is a red-herring. Second, we argue that the endorsement of moral contractarianism and the prohibition on indoctrination pull in different directions: if contractarianism is sound, then teachers or governments should be less worried about indoctrination than Hand suggests. Third, we argue that moral contractarianism is mistaken; teachers should look elsewhere for guidance on the moral norms and principles towards which they should direct their pupils.